PENGARUH LINGKUNGAN ORGANISASI TERHADAP KEPUASAN KERJA DI BPPT - djarwadi, djarwadi (Badan Pengkajian dan Penerapan Teknologi, 2011)
This research will investigate the influence of environmental work to job satisfaction BPPT officer. Research conducted directly by using questioner. Questioner allocated to a number of officer (210 responders) as sample. Questioner consisted of two shares that is organizational environment (environment work by 24 statements) and the job satisfaction (20 statements). Data processing conducted with multiple regression method, and use Statistical Packages for the Social Sciences (SPSS) program. Result of enumeration with backward elimination methods indicated that job satisfaction officer BPPT still be very low. The officer dissatisfy by environmental work is existing in this time. Organizational clarity,commitment, appreciation and spirit of group significant influences job satisfaction. Environmental work in BPPT is very big influences to officer job satisfaction.